An initial approach to the therapeutic dimension of Indian philosophy - Bennetts, Egdar (2025)
Several studies have addressed the comparison between Indian and Western philosophy from multiple perspectives. Although this work is not a comparative analysis, it is based on the conceptual framework applied to Western philosophy, developed by authors such as Pierre Hadot, Michel Foucault, and Martha Nussbaum, to investigate the therapeutic dimension of Indian philosophy. In this line, it is significant that researchers such as Jonardon Ganeri and Wilhelm Halbfass have undertaken analogous explorations. Their contributions demonstrate that Indian doctrines particularly –Nyāya and Vedānta– share with Hellenistic philosophies not only the therapeutic conception of philosophy, but also the notion that such therapy implies a "return to the self." This return aims to dismantle the illusion of the false, egotistical, and closed self (personal identity), freeing the subject from the alienations that separate them from their true self (ātman), linked to objectivity and universality. Vedantic concepts such as ārogya and svāsthya also capture this same idea, referring both to a “state of coinciding with oneself” and to the Indian ideal of liberation (mokṣa), typically understood as the supreme cure.